Analisis Kontrastif Nazonazo dan Tatarucingan: Permainan Kata Dalam Masyarakat Jepang dan Sunda - Eman Suherman; Alyarizki Dushanta; Amelia Putri Islami (Japanology: The Journal of Japanese Studies, 2025)
Traditional riddle games such as nazonazo in Japan and tatarucingan in Sunda, Indonesia, have long been used as a means of entertainment and language and cultural education, but have not been studied in depth in terms of comparative form and thematic vocabulary meaning. This study aims to analyze the similarities and differences in linguistic form, as well as the meaning and cultural implications of these riddles. The method used is descriptive qualitative, with data consisting of 28 nazonazo riddles collected online and 19 tatarucingan from books, as well as interviews with Sundanese informants, which were then analyzed using matching and distribution methods to find lexical patterns and linguistic structures. The results show that both nazonazo and tatarucingan prioritize everyday vocabulary and wordplay techniques based on puns, double meanings, and light creative logic. However, nazonazo offers more phonetic variations, visual characters, and foreign loanwords with global nuances, while tatarucingan emphasizes closeness to local experiences, exploration of sounds, and concrete metaphors and comparisons to everyday reality. These findings show that the tradition of wordplay in both cultures not only provides entertainment, but also plays an important role as a medium of education, inheritance of values, and formation of the unique social identity of each community.